The Efficacy Of Sports Management Clubs And Their Role In The Success Of Sports Professionalism In Algeria - Tebbani, ali (sports creativity, 2025)
Through the study of the management and management of sports clubs and their role in the development of sport in light of professionalism and requirements Management has become one of the fundamental goals and the future is determined by the present. The economic, social, political, cultural and technological transformations and changes have transformed the old administration into a modern administration operating under the change and the high motivation of modern technology and information society. The sports administration and management in clubs is one of the most important areas that relate to all aspects of the nature and life of individuals as it is considered a successful method in setting the objectives of individuals in a scientific way studied and achieved and if the absence of management and management in the lives of people and individuals solved randomness and failure to succeed and progress. It is noted here that professional sports in Algeria did not care about the development of human resources and rehabilitation because it is able to achieve the goals and the development of administrative policies in scientific methods and a systematic and consistent with them to achieve them and must be flexible and specific and clear, especially in light of sports professionalism and requirements and the study aimed to find out:  To know the selection policy and the appointment of human resources role in the development and success of sports professionalism.  To know the administrative composition of human resources role in the success of professional sports.  To know whether the adoption of a new administrative policy contributes to the success of sports professionalism.